A MODEL WITH KNOWLEDGE EXTERNALITIES AND EDUCATIONAL POLICY - VASILEV, Aleksandar (Theoretical and Practical Research in Economic Fields, 2021)
We utilize a standard endogenous-growth model with knowledge spillovers (the “k-K” model). We characterize the optimal Balanced Growth Path (BGP), and compare it to path under market competition. In the presence of externalities, markets fail. One way to restore efficiency is to subsidize knowledge accumulation, and finance the subsidy by taxing final consumption.